Pembelajaran Mandiri Perspektif Sosiologi Antropologi Pendidikan - I Gusti Ngurah Triyana (Purwadita : Jurnal Agama dan Budaya, 2021)
The purpose of this literature review research is to find out about independent learning from the perspective of sociology and anthropology of education. The method used is a literature review of various research journals that make independent learning, sociology and anthropology the objects of research. The results of the literature review show that education is categorized into formal education. Informal and non-formal are products of social interaction between humans in developing their individual and social potential. Culture becomes the estuary of educational activities which are part of human social life. Sociological and anthropological theories can be used to see human development consciously through activities called education which can not only be organized by official institutions, but can now be carried out independently in an effort to gain access to education from various channels. Keywords: Independent learning; sociology; anthropology